Analisis Kehilangan Hasil Sayuran Daun Teknologi Hidroponik (Studi Kasus: PT Bara Cipta Kreasi - Nurfikri, Irman; Perdana, Tomy (Universitas Galuh, 2026)
Food loss of yield in leafy vegetables at various stages causes financial losses for PT Bara Cipta Kreasi. The purpose of this study is to find the percentage and identify the factors that cause yield loss in the leafy vegetable supply chain and methods that can be used to reduce yield loss at PT Bara Cipta Kreasi. The study was conducted at PT Bara Cipta Kreasi in one of its business units, Bara Hidro, located in Bandung City, West Java. A qualitative design and case study were employed, along with observations and interviews to collect data for this research. This study utilized Pareto Diagram analysis, Root Cause Analysis (RCA), and Causal Loop Diagram (CLD). The results of the study indicated that the leafy vegetable commodity supply chain experienced a decrease in lettuce yield at Bara Hidro, reaching 23.2% and 31% for lettuce, 17.5% and 17.4% for pakcoy, 12.4% and 15.4% for water spinach for delivery to Borma and Tosama supermarkets, which impacted income in Bara Hidro with losses of Rp3,856,800 for lettuce, Rp1,864,800 for pakcoy, and Rp1,262,400 for water spinach. Human Resources (HR) and Plant Disturbing Organisms (OPT) are the main causes of yield loss in Bara Hidro. To reduce yield loss, it is recommended to adopt a preventive approach based on the circular economy, such as converting agricultural waste into organic fertilizer.